Erebonyx catacumbae, n. gen. et sp.: a blind, troglobitic cricket from Brazil (Orthoptera, Grylloidea, Phalangopsidae) - de A. G. De Mello, Francisco [UNESP]; Ferreira, Rodrigo Lopes (Magnolia Press, 2021)
Erebonyx catacumbae, new genus and species of a troglobitic phalangopsid cricket are described from Brazil. Few specimens were collected from a limestone cave located in the municipality of Campo Formoso, northern State of Bahia, in a semi-arid zone characterized by the Caatinga vegetation. A brief discussion on troglomorphisms is provided, as well as some ecological remarks and potential threats for this species.
Keywords: Cave cricket; Description; Neotropics; New genus; Speleology; Troglobite